Monetary policy transmission in the euro area: any changes after EMU? - Ignazio Angeloni; Michael Ehrmann (European Central Bank (ECB), 2003)
We examine the euro area monetary policy transmission process using post-1999 data, with two main questions in mind: has it changed after and because of EMU and, if so, is it becoming homogeneous across countries. Given the data limitations, we concentrate on three blocks of transmission: the banking, interest-rate and asset-market channels. We find evidence that the transmission through banks has become more potent and homogeneous across countries because of EMU. On the financial-market channels, our evidence is somewhat weaker but suggestive. The interest-rate channel appears to have changed even before EMU, and to now affect national economies in a broadly similar way. The asset-market channel (proxied by the stock-market effects of monetary policy) also seems to work rather homogeneously across national markets (no comparison with pre-EMU is available here). A positive answer to both questions raised above represents, in our view, the best working hypothesis under current knowledge.
Keywords: E43; E52; G21; 330; bank and financial integration; euro; Monetary policy transmission